MEDIA PEMBELAJARAN KELISTRIKAN PADA BATERAI BERBASIS MOBILE (STUDI KASUS DI PROGRAM STUDI MESIN OTOMOTIF POLITEKNIK TEDC BANDUNG) - Syani, Mamay; Hermawan, Tarwan (Jurnal TEDC, 2022)
Automotive Learning in TEDC Bandung Polytechnic Automotive Machine Study Program still uses learning modules as a medium to help learn. Based on the results of observations on December 24, 2020 with lecturers and students in the Automotive Machinery study program of TEDC Bandung Polytechnic showed that teaching and learning activities using learning modules have not functioned optimally because by reading enough material makes students less effective in learning. Based on these problems, the creation of electricity media on mobile-based batteries is intended to help students to more easily understand and understand how to remove batteries in vehicles, how to charge batteries, how to maintain batteries and electricity in light vehicle batteries. This application is built using Adobe Animate. The method used in the development of this application is the Multimedia Development Life Cycle (MDLC). Based on the results of blackbox testing all the functions in this application can run as expected. While based on the results of UAT testing this system proved to be well received by students of the polytechnic automotive machinery study program with a percentage score of 85.6%.